Peran Perempuan Pekerja Buruh Kerupuk Dalam Meningkatkan Ketahanan Ekonomi Keluarga Di Desa Mangli, Kecamatan Kaliwates, Kabupaten Jember - Wahida, Nur; Mayangsari, Rika Ifana Putri; Nurhayati, Alfisyah; Arif, Muhammad Ridwan (CV. ITTC INDONESIA, 2024)
The role of women as cracker workers is one of the jobs that can increase the economic security of the family. The economic resilience of the family can be influenced by the contribution of women which has a big influence on the welfare of the family, especially in the economic sector, quite a few women work to help improve the economic resilience of their families. In this case, women play a dual role in the family where they not only take care of household work, but they can also participate in the public sector because the family's needs are increasing compared to the income they earn. The role played by women is called the role of working women. This research aims to determine the role of women cracker workers in increasing family economic resilience and the supporting and inhibiting factors of women cracker workers in increasing family economic resilience in Mangli Village. This research uses a qualitative approach with a descriptive study type of research. The research results show that there is a very large contribution from the presence of women cracker workers in increasing the economic resilience of the family, which with this contribution can help the family economy significantly and they do this to achieve economic stability and resilience in their families.